The Implementation of Scientific Approach in Teaching English Subject at Senior High School of Riau Province - Syahputra, Idham; Syarif, Hermawati; Rahmawita, Medyantiwi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This study aims to explain the application of a scientific method in teaching English at Riau Province’s State Islamic Senior High School 2 (MAN 2). This is a descriptive qualitative study. This study includes one instructor and students from class X. MS.1. Techniques for gathering data include observation, interviews, and documentation. Techniques for data analysis include data reduction, data display, and data verification. The findings of this study suggest that the scientific approach is being used in the teaching of English at State Islamic Senior High School 2 in Riau Province, with the five phases being watching, inquiring, experimenting, associating, and communicating. There are various issues that either stymie or help use the scientific approach in teaching English topics. The time required in five components of the scientific method is an impediment. The next impediment is the material used. Factors that aid in implementation are; interesting material and student effectiveness.